Potential Fossilized Sulfide-Oxidizing Bacteria in the Upper Miocene Sulfur-Bearing Limestones From the Lorca Basin (SE Spain): Paleoenvironmental Implications - Andreetto, Federico; Dela Pierre, Francesco; Gibert, Luis; Natalicchio, Marcello; Ferrando, Simona (Frontiers in Microbiology, 2019)
The sulfur-bearing limestones interbedded in the upper Miocene diatomaceous sediments (Tripoli Fm.) of the Lorca Basin (SE Spain) are typified, as other Mediterranean coeval carbonate and gypsum deposits, by filamentous, circular and rod-shaped microstructures of controversial origin. These features have been interpreted both as faecal pellets of brine shrimps and/or of copepods, remains of algae or cyanobacteria and fossilized sulfide-oxidizing bacteria. To shed light on their origin, a multidisciplinary study including optical, UV and scanning SEM electron microscopy, Raman microspectroscopy and geochemical (C carbon and O oxygen stable isotopes) analyses has been carried out on three carbonate beds exposed along the La Serrata ridge. The different composition of the filamentous and circular objects with respect to the rod-shaped microstructures suggest that the former represent remains of bacteria, while the latter faecal pellets of deposit- or suspension-feeder organisms. Size and shape of the filamentous and circular microfossils are consistent with their assignment to colorless sulfide-oxidizing bacteria like Beggiatoa (or Thioploca) and Thiomargarita, which is further supported by the presence, only within the microfossil body, of tiny pyrite grains. These grains possibly result from early diagenetic transformation of original sulfur globules stored by the bacteria, which are a diagnostic feature of this group of prokaryotes. The development of microbial communities dominated by putative sulfide-oxidizing bacteria at Lorca was caused favoured by hydrogen sulfide flows generated through degradation of organic matter by sulfate-reducing bacteria thriving in underlying organic-rich sediments.